Comparison And Contrast of Retirement Attitude and Personal Pension Purchase Behavior Between Group Aged 26 to 30 and Group Aged 31 to 35 in Taiwan - Lai, Yu-Ju (2008)
A majority of previous research on retirement has primarily focused retirees or workers approaching retirement age from the perspective of their attitudes towards job and their lack in financial plan for retirement. In order to look into the relationship between retirement perceptions and pension purchase decision, the research aims to understand age difference of younger generations perceptions about retirement, the information, situation, and performance factors that would influence the decisionmaking of pension product. Further researches of the confidence in meeting needs for retirement and making pension-purchase decision are served as contrasts to people's attitude towards retirement and pension-purchase decision respectively. The research methods involved survey questionnaires. The data analyses were descriptive statistics. The major findings suggest that respondents of different ages demonstrated rather similar pension-purchase pattern even though their perceptions about retirement are quite different. Information Channel, situational factors and performance factors of decision-making on pension purchase are also discussed. The results of the study may help to stimulate pension providers to promote pension products more effectively and to the possible benefits of educating people for a better planning for retirement.